2020
DOI: 10.3390/ijerph17155518
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation between Accelerometers and Heart-Rate Monitorization during Exercise Session in Older Adults

Abstract: Aging is increasing worldwide; hence, aging-related health is also more relevant. Well-programmed physical exercise is now an indispensable tool to achieve active aging and preserve older people’s health. Such “well-programmed” exercise requires efficient and useful tools to measure the activity. The objective of this study is to evaluate the effectiveness of accelerometers to estimate two different intensities of physical exercise in older people. Thirty-eight subjects (64.5 ± 5.3 years) were measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Gait training using parallel bars or on a treadmill with minimal arm swing may also have been poorly detected. A study on the relationship between accelerometer and HR monitor measurements in older adults during exercise sessions found that an accelerometer placed on the hip failed to capture exercises involving balance and neuromotor function ( 31 ). This suggests that the position of the accelerometer should consider the specific exercises performed during rehabilitation sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Gait training using parallel bars or on a treadmill with minimal arm swing may also have been poorly detected. A study on the relationship between accelerometer and HR monitor measurements in older adults during exercise sessions found that an accelerometer placed on the hip failed to capture exercises involving balance and neuromotor function ( 31 ). This suggests that the position of the accelerometer should consider the specific exercises performed during rehabilitation sessions.…”
Section: Discussionmentioning
confidence: 99%
“…It involves three key components, namely, health, participation, and security, which have been extensively studied by academics. Health refers to lowering disease induced by ageing, hence, a well-designed physical activity location is a crucial strategy to protect the health of older adults [14]. Participation signifies that older adults may engage in activities according to their abilities, needs, and preferences, and may even contribute to society [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, alternative metrics like “activity count,” moving SD of acceleration (MSDA), or root mean square might be more appropriate for quantifying activity in certain contexts [ 15 - 17 ]. Prior studies have shown that heart rate and acceleration-measured activity values can behave differently [ 18 ], and that these indices can complement each other in estimating energy expenditure [ 19 , 20 ]. Thus, simultaneous measurement of these indices may offer valuable insights into the activity patterns of patients who had strokes.…”
Section: Introductionmentioning
confidence: 99%